Prospects For the Development of Ecological Tourism in Uzbekistan - Tlepbergenova Periyzat No’kisbaevna (Zien Journals, 2021)
This article provides an overview of the prospects for the development of ecotourism in Uzbekistan and the purpose of the development of ecotourism.
Keywords: Ecotourism; Innovative; Ecosystem; Ecotourism Resource